Pengaruh Disiplin Kerja dan Komunikasi Interpersonal terhadap Kinerja Pegawai pada Badan Kepegawaian Daerah Provinsi Jawa Barat - Nur Siti Aisah; Allya Roosallyn Assyofa; Firman Shakti Firdaus (Bandung Conference Series: Business and Management, 2023)
ABSTRACT. Employees who have a full contribution are good employees in their performance. If the results of the work he does meet the target, it means that the employee can fulfill the responsibilities delegated by his organization. Employee performance can be affected by obedience to time and responsibility in work discipline. In addition to improving employee performance, employees need to be open, provide empathy, provide support, positive feelings and understanding or similarities in interpersonal communication. The method in this study uses a quantitative method with a descriptive and verification method approach and operates calculations using the SPSS version 25 program. The variables in this study are Work Discipline, Interpersonal Communication, and Employee Performance. The collection of data obtained through observation, interviews, questionnaires. The sampling technique in this study used probability sampling with random sampling technique. Respondents in this study were 102 employees at the Regional Civil Service Agency of West Java Province. Based on the results of the study: 1) Work discipline at the West Java Provincial Civil Service Agency is included in the very high category 2) Interpersonal Communication at the West Java Provincial Personnel Agency is included in the very high category 3) Employee Performance at the West Java Provincial Personnel Agency is included in the category very high 4) Work discipline has a positive effect on employee performance at the Regional Civil Service Agency of West Java Province. 5) Interpersonal communication has a positive effect on employee performance at the Regional Civil Service Agency of West Java Province. 6) Work discipline and interpersonal communication simultaneously have a positive and significant effect on employee performance at the Regional Civil Service Agency of West Java Province. So it can be concluded that there is an influence between work discipline and interpersonal communication on employee performance at the Regional Civil Service Agency of West Java Province. Abstrak. Pegawai yang memiliki kontribusi penuh adalah pegawai yang baik dalam kinerja nya. Apabila hasil kerja yang dilakukannya memenuhi target, berarti pegawai tersebut dapat memenuhi tanggung jawab yang telah dilimpahkan oleh organisasi kepadanya. Kinerja pegawai dapat dipengaruhi oleh ketaatan waktu dan tanggung jawab dalam disiplin kerja. Selain itu untuk meningkat kinerja pegawai, maka pegawai perlu terbuka, memberikan empati, meberikan dukungan, rasa positif serta kesetaraan atau kesamaan dalam komunikasi interpersonal. Metode dalam penelitian ini menggunakan metode kuantitatif dengan pendekatan metode deskriptif dan verifikatif serta mengoperasikan perhitungan dengan menggunakan program SPSS versi 25. Pengumpulan data yang diperoleh yakni melalui observasi, wawancara, angket. Teknik pengambilan sampel dalam penelitian ini menggunakan probability sampling dengan Teknik sample random sampling. Responden pada penelitian ini adalah pegawai di Badan Kepegawaian Daerah Provinsi Jawa Barat sebanyak 102 orang. Berdasarkan hasil penelitian: 1) Disiplin kerja di Badan Kepegawaian Daerah Provinsi Jawa Barat termasuk dalam kategori sangat tinggi 2) Komunikasi Interpersonal di Badan Kepegawaian Daerah Provinsi Jawa Barat termasuk dalam kategori sangat tinggi 3) Kinerja Pegawai di Badan Kepegawaian Daerah Provinsi Jawa Barat termasuk dalam kategori sangat tinggi 4) Disiplin kerja berpengaruh positif terhadap Kinerja pegawai di Badan Kepegawaian Daerah Provinsi Jawa Barat. 5) Komunikasi interpersonal berpengaruh positif terhadap Kinerja pegawai di Badan Kepegawaian Daerah Provinsi Jawa Barat. 6) Disiplin kerja dan Komunikasi interpersonal secara simultan berpengaruh positif dan signifikan terhadap Kinerja pegawai di Badan Kepegawaian Daerah Provinsi Jawa Barat. Maka dapat disimpulkan bahwa terdapat pengaruh antara Disiplin kerja dan komunikasi interpersonal terhadap Kinerja pegawai di Badan Kepegawaian Daerah Provinsi Jawa Barat.